2020
DOI: 10.1111/srt.12906
|View full text |Cite
|
Sign up to set email alerts
|

Stereophotogrammetry to reveal age‐related changes of labial morphology among Chinese women aging from 20 to 60

Abstract: Background The lip is of important aesthetic value and highly subjected to aging. Collecting anthropometric baseline data and understanding age‐related changes of labial morphology can help with diagnosis of deformity, assessment of aging, and planning of cosmetic procedures. Many studies have focused on Caucasians, while there is a lack of anthropometric data on Chinese women. Methods A total of 169 women were enrolled in this cross‐sectional study and divided into four consecutive age groups. Linear distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…In addition to providing objectivity in evaluating volumetric enhancements, 3-D imaging is a useful tool to measure and assess linear and angular variables in facial aesthetic surgery. The 3-D stereophotogrammetry system used in our study (VECTRA M3) has been reported to be repeatable, giving accurate measures within the references established in several studies [ 9 , 10 ], with key facial angles presenting excellent intraclass correlation coefficient values [ 11 , 12 ]. However, it should be noted that the 3-D volume estimation in the study cannot be fully supported by precision in reproducibility since this system reads and interpolate the 3-D mesh data to calculate the theoretical surface volume of the closed area, instead of measuring the real volume of the lips.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In addition to providing objectivity in evaluating volumetric enhancements, 3-D imaging is a useful tool to measure and assess linear and angular variables in facial aesthetic surgery. The 3-D stereophotogrammetry system used in our study (VECTRA M3) has been reported to be repeatable, giving accurate measures within the references established in several studies [ 9 , 10 ], with key facial angles presenting excellent intraclass correlation coefficient values [ 11 , 12 ]. However, it should be noted that the 3-D volume estimation in the study cannot be fully supported by precision in reproducibility since this system reads and interpolate the 3-D mesh data to calculate the theoretical surface volume of the closed area, instead of measuring the real volume of the lips.…”
Section: Discussionsupporting
confidence: 68%
“…The 3-D imaging system used in this study was VECTRA M3 (Canfield Scientific, Parsippany-Troy Hills, NJ, USA). The accuracy and reproducibility of results obtained using this system have been demonstrated in many works [ 9 , 10 , 11 , 12 ]. This system has also been used to measure volumetric changes after lip filler injections [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 87%
“…The authors have been working on the clinical application of 3D anthropometry and agreed that the portability of a 3D imaging system brought great convenience to both clinicians and patients (19,20). The authors worked with engineers to develop a novel iPad/iPhone application for 3D photography.…”
Section: Discussionmentioning
confidence: 99%
“…This technology allows higher resolution cameras and accuracy depends on the pixel distance on the field of view instead of fringes distance. Although techniques based on stereophotogrammetry are of high interest and validated, [23][24][25] the privilege was given here to fringe projection-based systems since they provide full field, accurate, and high-resolution images prone to being further easily processed.…”
Section: Aeva-he and Dermatop Technologiesmentioning
confidence: 99%